Factor XIII Deficiency: An Update - Schroeder, Verena; Kohler, Hans P. (Seminars in Thrombosis and Hemostasis, 2013)
Confirmation of suspected congenital factor XIII (FXIII) deficiency still represents a diagnostic challenge in the field of rare bleeding disorders. Because of the lack of awareness and difficulties associated with timing of blood sampling, FXIII laboratory assays, and interpretation of laboratory results, diagnoses of FXIII deficiency are still missed all over the world with potentially fatal consequences from severe bleeding complications. Better knowledge of FXIII biochemical properties and function and understanding of the principles and limitations of FXIII laboratory assays can prevent missed diagnoses, and patients will benefit from better care. This review gives a detailed overview and update about congenital FXIII deficiency, its epidemiology, and molecular genetics. It highlights the importance of newer specific FXIII assays and their principles to avoid any missed diagnosis of FXIII deficiency. This review also gives an update on the therapeutic options for patients suffering from this rare but life-threatening disease.
Keywords: factor XIII; rare bleeding disorders; congenital FXIII deficiency; transglutaminase